Handbook of central banking, financial regulation and supervision : after the financial crisis - Eijffinger, Sylvester C. W.; Masciandaro, Donato (Cheltenham, Glos, UK ; Northampton, MA : Edward Elgar, 2011)
This stimulating and original Handbook offers an updated and systematic discussion of the relationship between central banks, financial regulation and supervision after the global financial crisis.
Includes bibliographical references and index.
oif 11/06/15
Loan
Keywords: Banks and banking, Central; Central banking - regulation; Central banking - supervision